If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 92 + -4x = 14x + 22 Reorder the terms: 92 + -4x = 22 + 14x Solving 92 + -4x = 22 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 92 + -4x + -14x = 22 + 14x + -14x Combine like terms: -4x + -14x = -18x 92 + -18x = 22 + 14x + -14x Combine like terms: 14x + -14x = 0 92 + -18x = 22 + 0 92 + -18x = 22 Add '-92' to each side of the equation. 92 + -92 + -18x = 22 + -92 Combine like terms: 92 + -92 = 0 0 + -18x = 22 + -92 -18x = 22 + -92 Combine like terms: 22 + -92 = -70 -18x = -70 Divide each side by '-18'. x = 3.888888889 Simplifying x = 3.888888889
| 9x^2=21x | | 2x+20=4x+6 | | x(3x-2)(x+6)= | | (3s-2)(4s+4)= | | 7x+32=x^2+4 | | 3.42/34.2 | | 3.42/24.2 | | 12=x/11 | | 8c*3v= | | -36x^2+96x-36=0 | | 2(5x+3)=4x-10 | | 1/6=6x | | 20x=460 | | 6=-3/5(4)+b | | 6=-3/5(4) | | -2x-6y=-74 | | 8x+3=6x+33 | | x+x+8+2x=240 | | 6x-(4x+3)=7 | | 6.3x=18.9 | | 9t^3+15t^2+t-6=t^2+t-6-3t^3 | | -12x^3+48x^2-36x=0 | | 8x+47=8(x+4) | | 7(4x-9)=40 | | 3x+6=-5-1x | | 3x^3+4x^4-6x^5-9x^6+14x^7-6x^8+x^9=0 | | ((a^4)/(2a^2-4a^4))*((8a^3+1)/(2a+4a^2)) | | 7(3x-9)=34 | | x-15=31 | | 5(7x-9)=20 | | 14-3x=-16 | | 6/7x-1/4x+10=11/14 |